Analysis Implementation Contract Murabahah at the Ummahat Al- Kaffah Sharia Cooperative Binjai Perspective of Fatwa No. 04/DSN-MUI/IV/2000 Concerning Murabahah - Riskyka, Riskyka; Iqbal, Muhammad Nur (Journal of Law, Politic and Humanities, 2025)
The purpose of this study is to evaluate the implementation of the murabahah contract at the Ummahat Al-Kaffah Binjai Sharia Cooperative and assess its compliance with the DSN-MUI Fatwa No.04/DSN-MUI/IV/2000 concerning murabahah. The study employs a qualitative method, which involves gathering descriptive data in the form of spoken or written words from people or observable behavior. Specifically, the research is empirical, aiming to observe and analyze how the law is applied in society. Data collection was conducted through interviews with informants to obtain direct information. The findings reveal that the cooperative allows its members to purchase goods for murabahah financing, including motorcycles, laptops, mobile phones, and business capital. Overall, the implementation of the murabahah contract at the Ummahat Al-Kaffah Binjai Sharia Cooperative largely adheres to the DSN-MUI Fatwa, although there are discrepancies in the fatwa's provisions. Notably, the fatwa's point 4, which stipulates that the cooperative should purchase goods in its own name, is not followed as members buy the goods in their own name, which deviates from the fatwa's guidelines